Lower-Limb Lymphedema after Sentinel Lymph Node Biopsy in Cervical Cancer Patients - Cibula, David; Borčinová, Martina; Marnitz, Simone; Jarkovský, Jiří; Klát, Jaroslav; Pilka, Radovan; Torné, Aureli; Zapardiel, Ignacio; Petiz, Almerinda; Lay, Laura; Sehnal, Borek; Ponce, Jordi; et al. (Cancers, 2021)
BACKGROUND: To prospectively assess LLL incidence among cervical cancer patients treated by uterine surgery complemented by SLN biopsy, without PLND. METHODS: A prospective study in 150 patients with stage IA1-IB2 cervical cancer treated by uterine surgery with bilateral SLN biopsy. Objective LLL assessments, based on limb volume increase (LVI) between pre- and postoperative measurements, and subjective patient-perceived swelling were conducted in six-month periods over 24-months post-surgery. RESULTS: The cumulative incidence of LLL at 24 months was 17.3% for mild LLL (LVI 10-19%), 9.2% for moderate LLL (LVI 20-39%), while only one patient (0.7%) developed severe LLL (LVI > 40%). The median interval to LLL onset was nine months. Transient edema resolving without intervention within six months was reported in an additional 22% of patients. Subjective LLL was reported by 10.7% of patients, though only a weak and partial correlation between subjective-report and objective-LVI was found. No risk factor directly related to LLL development was identified. CONCLUSIONS: The replacement of standard PLND by bilateral SLN biopsy in the surgical treatment of cervical cancer does not eliminate the risk of mild to moderate LLL, which develops irrespective of the number of SLN removed.